Descriptions of Student Needs for Digital Physics Teaching Materials on Particle Dynamics: A Preliminary Study - Hidayati Hidayati; Putri Dwi Sundari; Defrizal Saputra; Silvi Yulia Sari; Nabilah Ikrimah Ayani (Postgraduate, University of Mataram, 2023)
This research describes the initial study to develop e-modules based on student perceptions. This type of research is descriptive which was conducted in seven high schools in Padang based on school level with 667 students as respondents. Data were obtained using a questionnaire of student needs for teaching materials consisting of four indicators, namely student characteristics, implementation of physics learning, use of teaching materials in physics learning, and student needs for teaching materials. The results showed that as many as 67% of students experienced difficulties in physics subjects, supported by 53% of teachers who provided feedback at the end of each physics lesson and 45% of teaching materials used were less varied, in other words 80% of students needed other learning resources containing text, images and learning videos that were studied independently. The results of this study are expected to be the basis for the development of e-modules and efforts to improve the quality of physics learning in high school.